2020
DOI: 10.1007/s10208-020-09454-z
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Bifurcations of Hamiltonian Boundary Value Problems Under Discretisation

Abstract: We show that symplectic integrators preserve bifurcations of Hamiltonian boundary value problems and that nonsymplectic integrators do not. We provide a universal description of the breaking of umbilic bifurcations by nonysmplectic integrators. We discover extra structure induced from certain types of boundary value problems, including classical Dirichlet problems, that is useful to locate bifurcations. Geodesics connecting two points are an example of a Hamiltonian boundary value problem, and we introduce the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…However, multisymplecticity is known to be necessary to preserve traveling waves of hyperbolic equations [30], and compact multisymplectic methods can preserve dispersion relations much better than non-multisymplectic methods or noncompact finite difference methods [5,34,33]. For boundary value problems, multisymplecticity restricts the types of bifurcations that can occur [31,32]. Because it is a local property, multisymplecticity is a strictly stronger property than the symplecticity obtained by integrating over space.…”
mentioning
confidence: 99%
“…However, multisymplecticity is known to be necessary to preserve traveling waves of hyperbolic equations [30], and compact multisymplectic methods can preserve dispersion relations much better than non-multisymplectic methods or noncompact finite difference methods [5,34,33]. For boundary value problems, multisymplecticity restricts the types of bifurcations that can occur [31,32]. Because it is a local property, multisymplecticity is a strictly stronger property than the symplecticity obtained by integrating over space.…”
mentioning
confidence: 99%
“…Indeed, the authors prove in [22] that the behaviour shown in figure 2 and 3 is universal. This means in any Hamiltonian boundary value problem with a generic hyperbolic or elliptic bifurcation any symplectic integrator will show a bifurcation diagram as on the left of figures 2 and 3 while any integrator which breaks the symplectic structure of the problem will show incorrect bifurcation diagrams which qualitatively look like those on the right of figures 2 and 3.…”
Section: Breaking Of Hyperbolic and Elliptic Umbilic Bifurcationsmentioning
confidence: 95%
“…If, additionally, the other integrals of motions are also captured, e.g. because they are of a simple form or arise from a simple symmetry, then a symplectic method captures the periodic pitchfork bifurcations exponentially well [22,section 4.5,Prop.7]. For a non-symplectic scheme for this to happen either all integrals must be of a special form or be coming from simple symmetries for the method to capture these automatically or we must enforce their preservation (e.g.…”
Section: Numerical Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in (McLachlan and Offen, 2020), D-series bifurcations, such as hyperbolic umbilic bifurcations, are stable bifurcations in families of boundary value problems for symplectic maps but unstable in more general classes of boundary value problems. Other bifurcations, such as fold, cusp, which belong to the A-series, are also stable in wider classes of boundary value problems.…”
Section: Theoretical Considerationsmentioning
confidence: 99%